Performance of Rubberized Concrete-filled Hollow Steel Column under Monotonic and Cyclic Loadings - Muhammad Najmi, Mohamad Ali Mastor; Mariyana Aida, Ab Kadir; Nurizaty, Zuhan; Mujedu, Kasali Adebayo; Mohd Zamri, Ramli; Putra Jaya, Ramadhansyah; Norhazilan, Md Noor; Mohamad Syazwan, Ahmad Shah (Polish Academy of Sciences, 2022)
Concrete-filled hollow steel (CFHS) has become more popular due to its advantages and benefits compared to reinforced concrete. This paper presents the experimental investigation on the performance of rubberized pozzolanic concrete-filled hollow steel column (RuPCFHS) under monotonic and cyclic lateral load in comparison to bare hollow steel column and normal concrete-filled hollow steel column (NCFHS). The test parameters included the type of concrete infill and the level of axial load. Modified rubberized pozzolanic concrete with comparable compressive strength to that of normal concrete was used. Two types of axial load conditions: no axial load and 20% axial load were considered in the testing. The test results indicate that the performance of the columns improved when concrete infill was introduced in the hollow steel. The application of axial loading also increased the capacity of the column specimens. RuPCFHS behaved with comparable performance with NCFHS in both monotonic and cyclic testing. RuPCFHS recorded the highest increment in the energy dissipation capability when 20% axial load was applied to the column when compared to the other specimens. The comparable performance indicated the possibility of RuPC as an infill material of CFHS and RuPCFHS as a structural component.